The Effect Of Ginger Water Brewing On Overcoming Emesis Gravidarum In The Working Area Of The Baiturrahman Community Health Center In Banda Aceh City - Silvi Savira; Maulida; Ully Muzakir; Gadis Halizasia; Eridha Putra (Teewan Solutions, 2025)
Emesis gravidarum is a common symptom ranging from discomfort to prolonged vomiting, affecting approximately 50-60% of pregnant women. The potential impacts of emesis gravidarum on pregnant women include decreased appetite, which can lead to malnutrition and dehydration, which can be dangerous for both mother and fetus. Data from the Baiturrahman Community Health Center in Banda Aceh City indicates that in 2024, 187 pregnant women (85.7%) experienced emesis gravidarum. The purpose of this study was to determine the effect of ginger water infusion on the management of emesis gravidarum in the Baiturrahman Community Health Center's working area in Banda Aceh City in 2025. The research method used was a quasi-experimental one-group pretest-posttest approach with a purposive sampling technique with a sample size of 30 pregnant women with emesis gravidarum in the Baiturrahman Community Health Center Work Area, Banda Aceh City. The time of this research was conducted on April 22 to May 8, 2025 with univariate and bivariate analysis with paired t-test. The results showed that before giving ginger, most of them experienced emesis gravidarum in the moderate category, namely 23 people (76.7%), while after giving ginger, most of them experienced emesis gravidarum in the mild category, namely 25 people (83.3%). Before being given ginger water infusion, the average emesis gravidarum score was 8.43, while after being given ginger water infusion, the average score became 4.73 with a decrease of 3.70 and a p-value of 0.000 < 0.05, so there is an effect of giving ginger water infusion on emesis gravidarum. It is hoped that health workers will implement the administration of ginger water as a complementary therapy in treating emesis gravidarum and also provide counseling about the benefits of ginger water for pregnant women.